Função dos canais de cálcio voltagem-dependentes dos tipos T e L nas respostas de defesa eliciadas pela estimulação elétrica da matéria cinzenta periaquedutal dorsolateral do rato - Subtil, Tatiani Andreatta (2023)
Stimulation of the dorsal half of the rat periaqueductal gray (DPAG) with 60-Hz pulses of increasing intensity, 30-μA pulses of increasing frequency, or increasing doses of an excitatory amino acid elicits sequential defensive responses of exophthalmia, immobility, trotting, galloping, and jumping. These responses may be controlled by voltage-gated calcium channel-specific firing patterns. Indeed, a previous study showed that microinjection of the DPAG with 15 nmol of verapamil, a putative blocker of L-type calcium channels, attenuated all defensive responses to electrical stimulation at the same site as the injection. Accordingly, here we investigated the effects of microinjection of lower doses (0.7 and 7 nmol) of both verapamil and mibefradil, a preferential blocker of T-type calcium channels, on DPAG-evoked defensive responses. Thresholds were recorded either 24 h before or 10 min, 24 h, and 48 h after drug microinjection. We analyzed both response proportions using logistic threshold analysis and response thresholds using repeated measures analysis of variance for treatment by session interactions. The data showed that the electrodes were all located within the dorsolateral PAG. Compared to the effects of saline, verapamil significantly attenuated exophthalmia, immobility, and trotting. Mibefradil significantly attenuated exophthalmia and marginally attenuated immobility while facilitating trotting. While galloping was not attenuated by either antagonist, jumping was unexpectedly attenuated by 0.7 nmol verapamil. These results suggest that T-type calcium channels are involved in the low-threshold freezing responses of exophthalmia and immobility, whereas L-type channels are involved in the trotting response that precedes the full-fledged escape responses of galloping and jumping.